Sinhalese Version of the Global Physical Activity Questionnaire for Community-Dwelling Older Adults: Reliability and Validity - Wickramarachchi, Bimba; Sidiah, Siop; Perera, Bilesha (Elsevier, 2021)
Background: A reliable and valid measurement of physical activity (PA) is vital for PA surveillance activities in community settings and for evaluating PA intervention programs targeted at older adults. This study assessed the reliability and validity of a Sinhalese version of the Global Physical Activity Questionnaire-version 2 (GPAQv2) adapted for community-dwelling older adults (aged 60+) in Sri Lanka. Methods: Cross-cultural adaptation and an assessment of content validity of the GPAQv2 were done. Indirect criterion validity (n = 210) and test-retest reliability (n = 40) of the tool were assessed. Content validity index, Spearman rank correlation coefficients and intra-class correlation coefficient (ICC) were calculated, and Bland– Altman plots were drawn. Results: The content validity index of the questionnaire was 0.82, an acceptable value. The 3600 turn test (r = –0.258, p= 0.03), and timed up-and-go test (r = –0.197, p= 0.02) were negatively correlated, whereas total balance (r= 0.241, P= 0.00), single leg stance (r= 0.206, p= 0.01), and instrumental activities of daily living score (IADL) (r= 0.244, p= 0.00) were positively correlated with the GPAQv2 scores of PA, confirming the indirect criterion validity of the Sinhalese version of the GPAQv2. The tool demonstrated favorable test-retest reliability (ICC = 0.713). The mean difference between the test and retest total PA scores was –302.6 MET/week, a slight overestimation of PA in the retest. Conclusions: The Sinhalese version of the GPAQv2 demonstrates acceptable reliability and validity. It is suitable for use in PA measures among community-dwelling older adults in Sri Lanka